Career Skills Readiness of Chinese Students Majoring in Digital Media Art and Design: A Groundwork for Skills Enrichment Program - Chen, Hanhua; Layla P. Padolina (International Journal of Social Sciences and Public Administration, 2024)
With the rapid development of Internet digital information, mobile applications, digital media and website construction have become highly popular and popular, especially with the popularity and drive of smart phones, digital media has become an inseparable element of public life, and Chinese digital media art and design (hereinafter referred to as "China digital Media major") has become the mainstream of college majors in China. The object of enrollment expansion, resulting in uneven student talent. This paper discusses how to professionalize digital media students under the advantages of mainstream majors, how to realize the effective connection between college training and enterprise needs, and how to realize the integration of production and education. The vocational skills readiness of Chinese digital media majors can be obtained through the questionnaire survey of employers and students in related majors. The results will be used as the basis for the professional skills enrichment plan to help students better understand the needs of employers, carry out vocational skills learning with plans and goals, and achieve the ultimate purpose of employment.